2020
DOI: 10.1016/j.eneco.2019.104560
|View full text |Cite
|
Sign up to set email alerts
|

The response of CO2emissions to the business cycle: New evidence for the U.S.

Abstract: This paper investigates the response of CO 2 emissions to the business cycle for the U.S. on a monthly basis between 1973-2015. Using a rolling-regression approach, we find that the emissions elasticity with respect to GDP is not constant over time, irrespective which filtering method, such as the Hodrick-Prescott, the Baxter-King, the Christiano-Fitzgerald or the Butterworth filter has been employed. In order to check whether or not emissions react differently during normal and recession times, next, we emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…They found that anticipated investment technology shocks, unanticipated technology shocks, and government spending and monetary policy shocks accounted for 25, 10, and 1% of the changes in emissions, respectively. Using the Markov-switching approach and monthly data from 1973 to 2015, Klarl ( 2020 ) showed that emissions are significantly more elastic during recessions than in normal times and the elasticity of emissions is above one in recession times and below one in normal times in the USA. Gozgor et al ( 2019 ) found a significant dependence structure between business cycles and CO 2 emissions using the time-varying copula and the Markov-switching models in the US economy from January 1973 to January 2017.…”
Section: Output Volatility and Co 2 Emissions: Theory And Literaturementioning
confidence: 99%
“…They found that anticipated investment technology shocks, unanticipated technology shocks, and government spending and monetary policy shocks accounted for 25, 10, and 1% of the changes in emissions, respectively. Using the Markov-switching approach and monthly data from 1973 to 2015, Klarl ( 2020 ) showed that emissions are significantly more elastic during recessions than in normal times and the elasticity of emissions is above one in recession times and below one in normal times in the USA. Gozgor et al ( 2019 ) found a significant dependence structure between business cycles and CO 2 emissions using the time-varying copula and the Markov-switching models in the US economy from January 1973 to January 2017.…”
Section: Output Volatility and Co 2 Emissions: Theory And Literaturementioning
confidence: 99%
“…The application of novel concepts constitutes innovation. Product and organizational innovation are distinct subcategories of innovation that can be distinguished from one another (Klarl, 2020 ). Despite the positive effects of innovation on production growth and cost reduction, it also has a deleterious influence on energy usage and carbon dioxide emission.…”
Section: Introductionmentioning
confidence: 99%
“…They found that anticipated investment technology shocks, unanticipated technology shocks, and government spending and monetary policy shocks accounted for 25, 10, and 1% of the changes in emissions, respectively. Using Markov-switching approach and monthly data from 1973 to 2015, Klarl (2020) showed that emissions are significantly more elastic during recessions than in normal times and the elasticity of emissions is above one in recession times and below one in normal times in the U.S. Gozgor et al (2019) found a significant dependence structure between business cycles and CO 2 emissions using the time-varying copula and the Markov switching models in the U.S. economy from January 1973 to January 2017. Although there was a high dependence regime during the recession episodes up to 1982, the low dependence structure regime became prominent after 1983.…”
Section: Output Volatility and Co 2 Emissions: Theory And Literaturementioning
confidence: 99%